2008
DOI: 10.1016/j.alcohol.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Wheel running, voluntary ethanol consumption, and hedonic substitution

Abstract: Few studies have examined the relationship between naturally rewarding behaviors and ethanol drinking behaviors in mice. Although natural and drug reinforcers activate similar brain circuitry, there is behavioral evidence suggesting food and drug rewards differ in perceived value (Bickel et al., 1995;DeGrandpre et al., 1993;Petry and Heyman, 1995). The primary goal of the present study was to investigate the relationships between naturally reinforcing stimuli and consumption of ethanol in ethanol preferring C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 35 publications
6
47
4
Order By: Relevance
“…However, other studies examining the effects of physical activity as a treatment for heavy alcohol use have not yielded positive findings in reducing problematic alcohol use (Kendzor et al, 2008;Weinstock et al, 2014). These mixed findings parallel the preclinical evidence showing that physical activity does not reliably decrease voluntary alcohol consumption (Crews et al, 2004;Ozburn et al, 2008;Werme et al, 2002a) and they highlight the need for determining the critical conditions under which treatment of alcohol use disorders may benefit from physical activity.…”
Section: Clinical Evidencementioning
confidence: 73%
See 1 more Smart Citation
“…However, other studies examining the effects of physical activity as a treatment for heavy alcohol use have not yielded positive findings in reducing problematic alcohol use (Kendzor et al, 2008;Weinstock et al, 2014). These mixed findings parallel the preclinical evidence showing that physical activity does not reliably decrease voluntary alcohol consumption (Crews et al, 2004;Ozburn et al, 2008;Werme et al, 2002a) and they highlight the need for determining the critical conditions under which treatment of alcohol use disorders may benefit from physical activity.…”
Section: Clinical Evidencementioning
confidence: 73%
“…While one can conclude firmly that physical activity has a protective effect on drug self-administration in laboratory animals, there appears to be at least three important caveats to this conclusion. First, in contrast to stimulant and opiate self-administration, oral consumption of alcohol is not decreased by access to a running wheel (Crews et al, 2004;Ozburn et al, 2008;Werme et al, 2002a), and at least one study found that exercise increases alcohol preference and intake in mice (Werme et al, 2002a). While it is not clear what factors account for the difference between alcohol and other drugs of abuse, the route of administration needs to be considered (oral vs. injection), as well as the caloric content of alcohol, which may play a role in intake following physical exertion.…”
Section: Subjectsmentioning
confidence: 99%
“…As already mentioned, while Millard and Dole [37] reported photoperioddependent alterations in ethanol intake in this strain, we failed to replicate this effect in a recent study [45], albeit using different lighting schedules. Since the animals in our study were housed in runningwheel cages, and since access to running wheels has been shown to influence ethanol intake [5,15,27,36,38], in the present study we maintained half the animals with continuous access to running wheels and half with locked running wheels. In addition to testing for possible photoperiod by running wheel interactions on ethanol intake, this also allowed assessment of circadian adaptation to photoperiod in the wheel-access animals.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The Author speculates that the similarity between the chemical cascade catalyzed by temporal food restriction and that induced upon drug ingestion may enable one to substitute the reward engendered by feeding for the reward which ordinarily accompanies intoxication. In the analogous context of alcohol addiction and exercise, Ozburn [41] has termed this concept "hedonic substitution". Given the hedonic enhancement associated with feeding restriction, it is possible that individuals ingesting illicit agents may experience an intensification of euphoria.…”
Section: Exposition Of the Amen Anti-addiction Interventionmentioning
confidence: 99%